PENGARUH LAPORAN KEBERLANJUTAN (SUSTAINABILITY REPORT) TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Novia Puspita; J. Jasman (Faculty of Economics and Business, Universitas Warmadewa, 2022)
This research has a purpose to examine the effect of sustainability reports on company value by profitability as a moderating variable. Population of this study is the mining sector listed on the Indonesia Stock Exchange for the period of 2016-2019. The purposive sampling method are used to obtain the research sample. The official website of each company and the Indonesia Stock Exchange website are used to obtain sustainability reports and financial reports in research data. The data analysis technique used is simple linear regression and moderated regression analysis. The research results are sustainability report has a significant positive effect on company value. Meanwhile, profitability has not role as moderator in the positive effect of sustainability report on the company value.